Socio-Economic Status of Women Labourer from Peshawar in Statistical and Islamic Context - Dr. Naseem Akhter (الآفاق اسلامی و تحقیقی مجلہ)
A comprehensive analysis investigates the economic lived experience of Pakistani women laborers in Peshawar from a statistical and Islamic viewpoint. Women who work informally at home encounter economic together with social barriers as well as legal hindrances starting from weak pay to uncertain employment and inadequate access to protection. This evaluation utilizes statistics to investigate the earnings, workplace situations, and financial inputs of these women regarding both family needs and societal demands. The study examines Islamic teachings about labor rights economic justice and gender equity together with the principles of fair wages and workplace dignity and social welfare protection. Research exposes how wage standards and workers' treatment under contemporary employment systems differ fundamentally from Islamic teaching which endorses economic equity combined with respectful worker treatment. The study indicates policymakers must establish new regulations to improve both workplace conditions and financial support for Peshawar women working in labor. The research binds statistical evaluation with Islamic religious concepts to establish a complete approach to managing the socioeconomic challenges that women workers encounter in this territory.